Cutaneous Maniestations In HIV Positive Paediatric Patients - Ullal, KR; Kondreddy, B; Kuruvila, M; Bhat, K (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Background: Over the past decade Human Immunodeficiency Virus (HIV) infection has emerged as a major cause of severe illness and death in childhood in the United States and throughout the world. CD4 cell count and CD4 cell percentage are key markers for determining disease progress and the risk for opportunistic infection (OI) in HIV-infected patients. Objectives: This study was carried out to analyze the cutaneous manifestations in HIV positive paediatric patients and to correlate their pattern and severity with CD4 count. Material and Methods: This was a hospital based study wherein all HIV positive patients in the paediatric age group were screened for cutaneous manifestations over a period of two years, CD4 counts were estimated and their severity and atypical presentations were correlated with the CD4 counts. Results: Out of the 104 children included in this study, 93 had cutaneous manifestations. Transplacental was the commonest mode of transmission. There was a significant risk of Grade III malnutrition (p=0.03). Dermatological manifestations were present in all with CD4 count less than 200. The highest mean CD4 count was for bacterial infections and the lowest was for oral candidiasis. The mean CD4 count for fungal infection, oral candidiasis and xerosis were statistically significant (p=0.001, 0.002, 0.025 respectively) Conclusion: This study shows that the prevalence of mucocutaneous manifestations increases with advanced immunosuppression in pediatric age group and help in early recognition of the infection. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10591 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014 pp.14-19